Women Empowerment through Microfinance in Sri Lanka: Evidence from Thunukkai DS Division, Mullaitivu District - Kabilrajh, T.; Yogendrarajah, R. (Sri Lanka Finance Association., 2023)
The research was carried out to investigate the impact of microfinance services on women's economic and social empowerment in the Thunukkai Divisional Secretariat at Mullaitivu District, Sri Lanka. A four-stage random sampling technique was used to select 70 women microfinance beneficiaries from Thunukkai Samurdi Bank. The results revealed that microfinance has a positive impact on women's empowerment. Furthermore, microfinance positively impacts women's economic empowerment even as micro-credit and non- financial services contributed significantly to women's economic empowerment while micro-saving and micro-insurance do not impact on economic empowerment of women. Further, microfinance has a positive impact on women's social empowerment, just as microcredit and micro saving significantly contribute to women's social empowerment; however, micro insurance and non-financial services do not significantly contribute to women's social empowerment. The study recommends that microfinance could be enriched women, which is the appropriate tool to empower women in Sri Lanka, and research results could also support academics who want to assume more research on microfinance and women's empowerment from the literature arising from the study of excessive worth, as it will also enhance the significance of the present literature. Furthermore, the findings of this study could serve as a basis for future researchers and policymakers to take further steps to improve microfinance, women's empowerment, and poverty relief in rural areas such as Thunukkai.
Keywords: Economic empowerment; Microfinance; Poverty relief; Social empowerment; Women empowerment